The Relevance of Alexander Sutherland Neil's Humanistic Education to the Merdeka Curriculum in Promoting Student Autonomy - Adnan Syah Sitorus; Asril Azhari Hasibuan (International Journal of Basic Educational Research, 2025)
Education that places student freedom and autonomy at the core of the learning process is becoming increasingly relevant in efforts to shape education that humanizes humanity. This article examines the relevance of Neill's educational thinking to the principles of the Merdeka Curriculum. This research is a literature review using a comparative qualitative approach, aiming to analyze Alexander S. Neill's thoughts on humanistic education and compare them with the Merdeka Curriculum principles, particularly in developing student autonomy. Data was collected through documentation techniques, namely by searching and selecting literature such as books and scientific articles published in relevant national and international journals using keywords such as "A.S. Neill," "humanistic education," "Summerhill School," "Merdeka Curriculum," and "student autonomy" in various scientific databases such as Google Scholar and Scopus over the past 10 years. The core concept of Neill's educational approach is student freedom. He believed that excessive pressure and control from teachers and the curriculum fostered anti-learning attitudes, dishonesty, and emotional damage in children. At Summerhill, students are not required to attend specific classes and can choose activities based on their interests and readiness. Some principles of the Merdeka Curriculum that support student freedom include emphasizing differentiated learning, the principle of freedom realized through the Pancasila Student Profile Strengthening Project (P5), and student-centered learning. Both place students as active subjects in the educational process, emphasize freedom's importance and encourage teachers to act as facilitators in a supportive learning environment. This relevance can be understood through the framework of humanistic education theory, particularly Abraham Maslow's view on self-actualization, Carl Rogers' perspective on student-centered learning, and the Self-Determination Theory of Motivation, which emphasizes the importance of autonomy, competence, and relationships in fostering intrinsic motivation.